(untitled) (Research, Society and Development, 2020)
Rock dust contains nutrients that can improve the nutritional development of plants. Thus, the objective was to evaluate the availability of phosphorus (P) and potassium (K) through rock powders collected in different locations and their effects on the development of corn plants. Three sources of rock powders were used [collected in Campo Alegre de Lourdes-BA (R1), Gilbués-PI (R2), and Cristalândia-PI (R3)], characterized by diffractometry, granulometry, and the dissolution of P and K in a thermodynamic process. After the physicochemical characterization of the powders, different doses (2.0; 6.0; 8.0 and 10.0 t ha-1) were applied to the soil to analyze its effects on corn plants. In the rock R1, the presence of muscovite (mica) and apatite (phosphates) was observed, in R2 the presence of muscovite (mica) and orthoclase (feldspar) and in R3 the presence of muscovite (mica) and microcline. The rocky dust materials showed dissolution of P and K in an acid medium in the aqueous extract. The rocks dust collected in Gilbués-PI improved the availability of P and K and favored the development of the aerial part of the corn plants.